Power, Trust, and Institution: Tax Authority VS Taxpayer in Indonesia - Sihotang, David Mondru (CV. Ridwan Publisher, 2020)
This study estimates tax compliance in a relationship between power of authority and trust in authority in Indonesia, and how institution plays key role to shape tax reform. Using the aggregate data of individuals and firms per region tax office in all provinces in Indonesia in 10 years of taxing period (2008-2017) in time-fixed effect model, we found that soft and medium approach in power of authority gives significant effect in increasing tax compliance. However, other findings show that the higher taxpayer income, the lower the tax compliance. In addition, Java, Bali and Nusa Tenggara still give higher compliance than the other location in Indonesia. Tax reform needs institution as a rule to adapt in taxpayer behavior and understand the compliance risk.